1983
DOI: 10.1037/0022-006x.51.6.864
|View full text |Cite
|
Sign up to set email alerts
|

Development and cross-validation of a short form for the WISC-R.

Abstract: The multiple linear regression method was used to derive a short form for the Wechsler Intelligence Scale for Children-Revised in a sample of 300 children receiving treatment and/or evaluation at a university-affiliated community mental health center. The predictive validity of this approach was examined via a crossvalidation that included 300 additional subjects taken from the same population, as well as two short-form regression equations taken from the work of Kennedy and Elder (1982), and a short form deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

1986
1986
1992
1992

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 11 publications
2
15
0
Order By: Relevance
“…As noted previously, Beck et al (1983) found relatively little shrinkage in the validities of short forms of the WISC-R that involved differential weighting when the regression equation based on data from one sample was applied to data from a different sample. As noted previously, Beck et al (1983) found relatively little shrinkage in the validities of short forms of the WISC-R that involved differential weighting when the regression equation based on data from one sample was applied to data from a different sample.…”
supporting
confidence: 55%
See 4 more Smart Citations
“…As noted previously, Beck et al (1983) found relatively little shrinkage in the validities of short forms of the WISC-R that involved differential weighting when the regression equation based on data from one sample was applied to data from a different sample. As noted previously, Beck et al (1983) found relatively little shrinkage in the validities of short forms of the WISC-R that involved differential weighting when the regression equation based on data from one sample was applied to data from a different sample.…”
supporting
confidence: 55%
“…Quite apart from my earlier study of short forms of the WISC (Silverstein, 1967), previous studies of short forms of the WISC-R provided a broad hint as to what the findings of the present study might be. Beck et al (1983) reported validities that ranged from .95 to .97 for several short forms, and validities in this same range when their multiple regression equations were cross-validated with data from different samples. The correlation using the two sets of weights was .997.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations